Existence of Positive Solutions for the Nonhomogeneous Schrödinger-Poisson System with Strong Singularity (Journal of Partial Differential Equations, 2021)
In this paper, a class of nonhomogeneous Schrödinger-Poisson systems withstrong singularity are considered. Combining with the variational method and Neharimethod, we obtain a positive solution for this system which improves the recent resultsin the literature.
Keywords: Schrödinger-Poisson system; strong singularity; positive solution; Nehari method.